Théorie et idéal de l’organisation muséale - Aurélien Joudrier (In Situ)
How is a museum organised? Because museums are all very different from each other, very few people have attempted to theorise museum organisation. Of course the main functions and objectives of museums have been studied but these studies have not always been linked together. French law does not stipulate any way of organising a museum except that all museums are expected to have a service for the reception of the public and for functions of diffusion, animation and cultural interpretation. The Louvre, alone amongst all of France’s museums, is the only one to be officially divided into separate departments. Museum administration tries to maintain an equilibrium between the different components of its staff, and professional and initial training. But it is very difficult to fit people the right job taking these three aspects into account. Consequently, many people in museums suffer from the fact that their actual job is not adapted to their qualifications. Organisational charts reflect the history of the institution and the way different services have been incorporated into it, but such chart are rarely questioned as to the efficiency. Looking at the examples of the Louvre and the Musée du Quai Branly, the museum’s mission in relation to its business organisation will be examined. A hypothetical ideal museum organisation is offered. The core of a museum is its collection, and the museum’s organisation should be centred on this idea. Three departments are essential to run a museum: a collection department, a security department and a technical department. All of these are managed by the direction which leads the museum and give it its general strategy. Curating and making collections accessible to the public are the only way for a museum not to lose sight of its objectives and fulfil its public service mission.